Approximate Compensation for Mutual Coupling in a Direct Data Domain Least Squares Approach using the In-situ Measured Element Patterns - Choi, Wonsuk; Sarkar, Tapan K.; Allen, Oliver E.; Asvestas, John S. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a new technique for an approximate compensation of the effects of mutual coupling among the elements of an array using the measured in-situ element patterns in a direct data domain least squares algorithm. In this paper, we consider the antenna elements in the phased array to have finite dimensions, i.e., they are not omni-directional radiators. Hence, the antenna elements sample and re-radiate the incident fields resulting in mutual coupling between the antenna elements. Mutual coupling not only destroys the linear wavefront assumption for the signal of interest but also for all the interferers impinging on the array. Thus, we propose a new direct data domain approach that partly compensates for effect of mutual coupling, specifically when the jammer strengths are comparable to that of the signal. For strong interferers, a more accurate compensation for the mutual coupling is necessary using the transformation matrix through the formation of a uniform liner virtual array.